Cognitive limits of social sciences and common sense - Dores, A. P. A. (V!rus, 2018)
The social sciences, like the common sense, have not been sufficiently emphatic in condemning the evil represented by the penitentiary system. The social sciences are averse to biologism, to the biological character of humanity; and to ideology, the way elites deceive submissive populations. Social theories end up integrating elites mission. António Damasio, with the biology of the mind as a starting point, challenges the social sciences to consider human nature: the emotional foundation which sustains consciousness, as different levels of existential reality based on the bodies and life that we are a result of. The scientific opening proposed by Damásio permits us to see the moral significance of modern prisons in a new light: how does the emotional background of sentences (retaliatory) supports the (good or bad) conscience (judicial and social) that institutionalizes the penitentiaries? From a social sciences perspective, this article presents a critique of the theoretical foundations that underlie the epistemic and institutional difficulty of admitting and fostering collaboration between the social sciences and the natural sciences, participating in Damasio's critique of biological theory.